Study of prescribing practices of injections in outpatients of a rural tertiary care teaching hospital - Rathod, Suvarna S.; Motghare, Vijay M.; Padwal, S. L.; Deshmukh, V. S.; Pore, Rakesh R.; Deshpande, Rushikesh; Bhamare, Chetanraj G. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Injections are probably the most common of all medical procedures. The combination of injection overuse and unsafe practices creates a major route of transmission of blood borne pathogenic infections. Unnecessary use of injections can also lead to unnecessary burden on the institution in terms of efficiency, infrastructure, staff requirement and poor utilization of resources. Monitoring and analysis of prescribing practices can help to achieve rational use of injections. The present study was carried out to study the injection prescription patterns in outpatients of a rural tertiary care teaching hospital, Ambajogai, Maharashtra, India. Methods: A cross sectional descriptive study was conducted for duration of two months and 744 prescriptions were randomly collected and analyzed. Results: The total number of injections prescribed in 744 prescriptions was 205. Most (71.70%) of the patients receiving them were above 35 years of age. The most common complaint for which the injections were prescribed was musculoskeletal pain (45.36%) followed by fever. About 155 (75.60%) prescriptions contained injection diclofenac which was the most commonly used drug followed by injection paracetamol (11.21%). There was a high tendency of using brand names in prescriptions (89.30%). Conclusion: The study revealed high proportion of use of injectable drugs. There was overuse of analgesic injections like diclofenac, most of which were unnecessary and irrational. This leads to unnecessary burden on the institution in terms of efficiency, infrastructure, staff requirement and poor utilization of resources. There is a need to develop local guidelines for injection usage along with educational sessions for prescribing doctors.